KEARIFAN LOKAL DAN TATA KELOLA RUMAH SAKIT - Andri Nur Rahman; Eny Hastuti; Liana Fitriani Hasymi; Abdurrahman Sidiq; Yandi Suharsono (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2026)
Hospitals do not only perform medical functions; they also operate within communities that hold distinct cultural values and customs, commonly referred to as local wisdom. This article presents a literature review aimed at: (1) identifying and analyzing the meaning of local wisdom from various references; (2) identifying and analyzing the forms of local wisdom implementation in the management and services of hospitals and other healthcare facilities; and (3) formulating a definition of local wisdom appropriate for healthcare service management. The review was conducted using a descriptive-qualitative literature review method on 15 sources, covering both foundational concepts of local wisdom and studies of its implementation in hospitals. The findings show that local wisdom refers to good values and customs rooted in local communities, which are dynamic in nature and may take tangible or intangible forms. Five hospital case studies from Indonesia — in Bali, Central Java, Maluku, and West Java — show that local wisdom is applied across three domains: spiritual, communication, and technical-service, with positive effects on patient satisfaction, hospital image, and staff teamwork. Based on these findings, an operational definition of local wisdom for healthcare service management is proposed: culturally rooted values and customs deliberately embedded into hospital policy and service delivery to build patient trust and comfort, without compromising clinical quality standards. This study also produces a practical checklist instrument for assessing the implementation of local wisdom in hospitals, intended for use by hospital administration students and practitioners alike.